A co-citation study of information security patents in the USPTO database. Issue 4 (29th October 2020) - Janavi, Elmira; Emami, Maryam
Abstract : Purpose: The goal of this study was to investigate the co-citation of information security patents in the United States Patent and Trademark Office (USPTO) database. Design/methodology/approach: This research is a scientometrics study that has been conducted using the co-citation analysis. The statistical population of the present study includes all patents of information security filed in the USPTO database from 1971 to 2015. As a result of this search, 30, 736 patents were retrieved. In this investigation, UCINET software and its complementary package (NetDraw) were employed to plot scientific maps. Findings: The findings of this study indicated an upward trend of patents in the field of information security between 1971 and 2015. The "California State" has the top world rank in information security inventions, followed by "Japan" and the "Washington State." "VAN WIE, DAVID M" is the most cited inventor in the field of information security. The analysis of inventors' co-citation data indicated that "ADAMS, NEIL- LITTLE" and "HERBERT ANTHONY" had the highest co-citation rates with each other and were ranked first. The survey of high-citation inventors based on centrality indices indicated that "LEACH, PAUL J" graded first in degree centrality, "BENALOH, JOSH D" in betweenness centrality and "BENALOH, JOSH D" in closeness centrality. Originality/value: The co-citation analysis of patents can show the most important patents and the relationships between them. Such analyses can be useful for large-scale policymaking or identification of existing gaps and attempting to address them.